Design of a turbulent wing for small aircraft using multidisciplinary optimisation - Stalewski, W.; Żółtak, J. (Archives of Mechanics, 2014)
Design process of a turbulent wing for small aircraft, using multidisciplinary and multi-objective optimisation, based on a genetic algorithm was presented. A generic parametric model of small aircraft wing geometry was developed. In the model, a wide class of wing geometries, with and without high lift devices, was described by a relatively small number of parameters. The optimisation method used the objectives and constraints typical for multidisciplinary wing design, and was applied to the design and optimisation of turbulent wing dedicated for small, two-propeller aircraft. The research was conducted within European Project CESAR. The results of the research have been discussed.